Evaluation of Account Receivables Management to Prevent Possible Company Losses as a Result of Uncollectible Accounts Receivables at PT Askrindo (Persero) of the Surakarta Branch Office - Azzahra Syafiya Syaebani; Vidia Ayu Satyanovi; Lina Nur Ardila; Andy Supriyadi (AKUMULASI: Indonesian Journal of Applied Accounting and Finance, 2022)
This research was conducted at PT Askrindo (Persero) of the Surakarta Branch Office. This study aimed to investigate the management of accounts receivable and the implementation of the management of accounts receivable running within the company whether they are in accordance with the policies in force in the company. This study uses descriptive data analysis method. The results of this study indicate that the implementation of accounts receivable management at PT Askrindo (Persero) of the Surakarta Branch Office, which includes the recognition, recording, classification, and accounts receivable management policies, has not followed the guidelines for accounts receivable management business issued by the company. First, the implementation of the recognition of trade receivables is in accordance with the guidelines for managing accounts receivables, which are recognized after the issuance of an insurance certificate/policy. Second, the implementation of recording accounts receivable complies with the guidelines for managing accounts receivables, which are recorded using the Askrindo Financial Management System (FMS). Third, the implementation of the classification of accounts receivable is consistent with the guidelines for managing accounts receivable, namely by classifying current, non-current, and loss accounts receivables. Fourth, the implementation of the accounts receivable management policy does not follow the guidelines for managing accounts receivable. The company has not implemented several policies according to the guidelines in the company.